Vivências de agentes comunitários de saúde na atenção a idosos acometidos por doenças crônicas - Marinês Tambara Leite; Sandra Dal Pai; Leila Mariza Hildebrandt; Luiz Anildo Anacleto da Silva (Universidade Federal do Ceará, 2016)
Objective: to understand which are the experiences of community health agents in the care of patients with chronic diseases. Methods: qualitative research carried out through the interview of 20 community health agents. Data were analyzed following the steps of content analysis. Results: the care for the elderly has limitations due to their low educational level, resistance to adhere to drug therapy and low frequency of visits to health facilities. Another reason is the aging process in itself that may compromise the ability of self-care and the development of daily activities. Conclusion: difficulties of community health agents were identified in the care of elderly people with chronic diseases due to low adherence to treatment and to the health service.